Well-defined oligosaccharides by mild acidic hydrolysis of hemicelluloses. (May 2015) - Chemin, Maud; Wirotius, Anne-Laure; Ham-Pichavant, Frédérique; Chollet, Guillaume; Da Silva Perez, Denilson; Petit-Conil, Michel; Cramail, Henri; Grelier, Stéphane
Graphical abstract: Highlights: Beechwood xylans were hydrolyzed by sulfuric acid to generate xylooligosaccharides. The acidic hydrolysis is controlled and reproducible. XOS have a DP of 6 with one acid glucuronic residue at the non-reductive chain end. XOS were fully characterized using NMR, SEC, MALLS, MALDI-TOS MS analyses. Abstract: The purpose of this study is to target well-defined xylooligosaccharides by controlled sulfuric acidic hydrolysis of beechwood xylans. Parameters such as sulfuric acid and xylan concentrations, hydrolysis duration and temperature have been investigated, allowing optimum conditions to be determined (0.7 M H2 SO4, 90 °C, 45 min). The obtained xylooligosaccharides show a well-defined structure and have been characterized using several techniques such as 1D and 2D nuclear magnetic resonance spectrometry and matrix-assisted laser desorption/ionization-time of flight mass spectrometry. This work demonstrated that mild acidic hydrolysis conditions enable the reproducible production of xylooligosaccharides containing, on average, six xylose units and only one 4- O -methyl- D -glucuronic acid unit likely positioned at the non-reductive chain-end.